(3CQLhRI aj fXe GdbVGjG GdNeSI hGdYTQjf dCHbQGW Ydi OdGdI GdehJs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3jG QH SQ de jRd eNRhfG ecJJeG Hjf GdhQi ecfhfG s
(3BNQgG (B:s
(3eHJhQ , hBNQ HjJ ehLhO efgG (B: (3hCjSQ GdEHWjf Ef YjfJG HgG NQGLkG ceOkG CMceJgG s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGdKIs
(3GfXQgG eY CQLhRI ai GdMejGJ Qbe (B" 380_382" (3hGfXQ CQLhRI ai YdGeGJ GdehJ Qbe(B" 303 "s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B17 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs